Is Malaysia facing negative deindustrialization? - Rasiah, R. (2010)
This paper seeks to examine whether Malaysia is facing negative deindustrialization by examining value-added, trade and productivity trends over the period 1990-2005. The evidence produced in the paper is concrete enough to confirm that Malaysia is facing negative deindustrialization. While it is typical, as part of the process of structural change, to see a rise and fall in the share occupied by manufacturing in the GDP, the evidence shows that Malaysia is indeed facing premature deindustrialization with a trend slowdown in manufacturing value-added, trade performance and productivity since 2000. Not only has the trade performance of manufacturing been falling, manufacturing labour productivity has also slowed down, with the key sectors such as electric-electronics, textiles and transport equipment showing either negative or low productivity growth since 2000. Malaysian industrial policies have been fairly successful in connecting with the global value chains of multinationals and in developing resource-based industries, but have not achieved the same success in stimulating their transformation to high value-added activities. The lack of effective institutional change, partly explained by ethnic policies, is advanced as the prime reason for the setting in of negative deindustrialization in Malaysia.